Better Understanding of Hydrogen Pellet Ablation Cloud Spectra through the Occupation Probability Formalism in LHD - Motoshi Goto; Gen Motojima; Ryuichi Sakamoto; Bernard Pégourié; Akinobu Matsuyama; Tetsutarou Oishi; Tomoko Kawate; Yasuko Kawamoto (Atoms, 2024)
We have recently incorporated the occupation probability formalism (OPF) in the simulation model [C. Stehlé and S. Jacquemot, Astron. Astrophys. 271, 348 (1993)] to have a smooth transition from discrete lines to continuum spectrum in the wavelength range near the Balmer series limit. We have analyzed spectra measured for the hydrogen pellet ablation cloud in the Large Helical Device with the revised model, and have found that the electron density in the ablation cloud has a close correlation with the electron temperature of the background plasma. This type of correlation is first confirmed in the present analysis and should give a new insight in the simulation studies of pellet ablation for the magnetically confined fusion plasma.